MONITORING OF HIGH-RISK NEWBORN: A CLINICAL PRACTICE OF NURSING IN THE CONTEXT OF PRIMARY HEALTH CARE (Fiep Bulletin - online, 2013)
Premature birth, low-birth-weight, complications during pregnancy and childbirth are factors contributing to the hospitalization of newborns in Neonatal Intensive Care Unit (NICU). They, after discharge from hospital, are showing the necessity of care in specialized care health services. In this case it is necessary that health professionals of Primary Health Care (PHC) offer them appropriate care. This study aims to identify the knowledge and technical and scientific skills of nurses who have worked at this level of health care with child at risk. Qualitative study, which used recorded interview to get the data. Three themes emerged from the data analysis: service organization of the follow up children and the child's discharge from the NICU in the basic health unit, nursing assessment of children at risk in the basic health unit, skills and difficulties of technical and scientific in the follow up of newborns in the primary care. Nurses showed topics about the child's health should to be addressed in continuing education and identified their difficulties in performing adequate services to children at risk and their families, resulting in an unsatisfactory service. As a possible strategy to the situation found, there is the continuing education for these professionals, which is a method to help address the needs identified in the reality under study.
Keywords: Child health; childcare; child risk.